Generative AI in Dentistry: Transforming Patient Care and Treatment Planning - Dr. Manisha Murella, Dr. Dhyaan Dharma, Dr. Shivani Neelam, Dr. Aya Misrabi, Dr. Anamika Shrikrishna Deshpande, Dr. Maiyra Wajid (South Eastern European Journal of Public Health, 2025)
Artificial intelligence (AI) is changing healthcare by advancing diagnostic accuracy, streamlining treatment planning, and enhancing patient care management. In dentistry, Large Language Models (LLMs) like Chat Generative Pre-Trained Transformer (ChatGPT) are proving to be invaluable for improving clinical decision-making and overall patient care. In this paper, we explore how ChatGPT is transforming the process of decision-making in the field of dentistry by providing diagnostic assistance, individualized management plans, and educational resources. The advantages include increased efficiency, enhanced precision, and increased accessibility that makes it an essential tool in today’s dental practice. Nevertheless, its application has to be coupled with professional judgment and a number of ethical issues. Adopting the use of ChatGPT in the right way in clinical practice helps dental practitioners to be in a position to provide better care to patients while upholding professional standards.